Effectiveness of Instructional Skills Training for TVET Instructors in Nepal: Evaluation through the Kirkpatrick Model - Rimal, Ishwor (Journal of Technical and Vocational Education and Training, 2025)
This study assesses the effectiveness of instructional skills training offered by the Training Institute for Technical Instruction (TITI), Nepal, using the Kirkpatrick Model. The four levels of evaluation of this model - reaction, learning, behavior, and results - were used to assess the effectiveness of the training conducted for the Technical and Vocational Education and Training (TVET) instructors. The quantitative method was applied for this study. Data were collected through a structured questionnaire and administered to 51 participants of instructional skills (IS) training. The findings showed that IS participants rated reaction at 4.00, learning at 2.76, performance at 4.3, and overall results at 4.00. The overall training effectiveness was 3.76. These scores were based on a five-point Likert scale, where 1 meant "strongly disagree" and 5 meant "strongly agree." In this regard, training reactions were positively impacted; the learning was moderately achieved; the trainers improved their performance; and the trained instructors’ outcomes was enhanced in the instructions. Finally, the training impacted positively to improve quality of the instruction in the teaching learning process.